(E)-2-Chloro-N′-(2-hydroxy-1-naphthylmethylene)benzohydrazide - Qiu, Feng (International Union of Crystallography, 2008)
In the structue of the title compound, C(18)H(13)ClN(2)O(2), a new Schiff base, the dihedral angle between the benzene and naphthyl ring system mean planes is 22.5 (2)°. The molecule has an E configuration about the C=N bond, and an intramolecular hydrogen bond involving the hydoxyl substituent on the naphthyl ring and the N′ atom of the hydrazide. The crystal structure is stabilized by intermolecular N—H⋯O hydrogen bonds, forming one-dimensional chains running parallel to the a axis.